Response of sand model under lateral dynamic loading - Tan, Zhi Qian. (2010)
Singapore, a multi-trade hub around the region with a land space of around 710.2km2 with a population density of 6814 people per square kilometer, is ranked the 3rd around the world. The country is built mainly on reclaimed land and is located about 400km away from a highly active earthquake belt, the Sumatra fault and subduction zone, where some of the greatest earthquakes have occurred in the past. Any major earthquakes around this region may thus, affect the nation causing economic losses.